Ciprofloxacin for the treatment of Cardiobacterium hominis prosthetic valve endocarditis - Lisa M. Avery; Catherine B. Felberbaum; Muhammad Hasan (IDCases, 2018)
Prosthetic valve endocarditis due to Cardiobacterium hominis is rare and recommended therapy includes a third generation cephalosporin. We report a case of Cardiobacterium hominis endocarditis post transcatheter aortic valve replacement in a patient with significant beta-lactam antimicrobial sensitivities who was successfully treated with ciprofloxacin monotherapy in conjunction with surgery.